Simultaneous bilateral spontaneous pneumothorax with congenital pleuro-pleural communication - Hata, Yoshinobu (Pioneer Bioscience Publishing Company, 2013)
A single pleural space can lead to serious simultaneous bilateral pneumothorax in cases of congenital or acquired pleuro-pleural communication. Here we report a 35-year-old man with bilateral pneumothorax. Chest computed tomography scans revealed a small air space between the esophagus and aorta, suggesting pleuro-pleural communication. Bilateral thoracoscopic bullectomy was performed. Repeated inspection revealed a 2-cm-long pleural window between the aorta and esophagus, which was closed with a collagen patch. Although congenital pleuro-pleural communication has been regarded as rare, as many as nine patients have been reported (if suspected cases are included). The lower middle mediastinum should be carefully inspected.